Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1984
DOI: 10.1115/84-gt-98
|View full text |Cite
|
Sign up to set email alerts
|

Gas and Liquid Fuel Injection Into an Enclosed Swirling Flow

Abstract: A swirler with good premixed performance has been tested with direct central propane injection and with direct central kerosene and gas oil injection using the swirler air for atomisation. The results have been compared with non swirling flow systems at the same test conditions. Direct propane injection results in a major extension of the stability limits compared with the premixed situation, but with liquid fuel injection the stability limits are generally worse than for premixed fuel and air. It is argued th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…The vane angle used, 45°, was the same as that previously used for axial swirlers (9)(10)(11)(12) and was well into the region where the swirl would generate an inner recirculation zone. It was a similar radial swirler design to that currently in use in the Ruston Tornado combustor.…”
Section: Radial Swirler Designmentioning
confidence: 99%
“…The vane angle used, 45°, was the same as that previously used for axial swirlers (9)(10)(11)(12) and was well into the region where the swirl would generate an inner recirculation zone. It was a similar radial swirler design to that currently in use in the Ruston Tornado combustor.…”
Section: Radial Swirler Designmentioning
confidence: 99%
“…Many of the proposed designs involve swirl based systems. Although these have some advantages, Ahmad et al (5)(6)(7)(8)(9) have shown that the NOx emissions and combustion efficiency of weak mixtures is not as good as in the present jet shear layer designs. The authors have extensively investigated various designs of jet shear layer fuelled systems for low emissions wide stability combustor primary zones (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 86%
“…Andrews et al (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) have investigated three lean primary zone designs that have shown promise, all of them based on fuel and air mixing in and flame stabilisation by jet shear layers. The first of these was a simple flat grid plate jet shear layer combustion system (4,5) with each shear layer individually fuelled.…”
Section: Introductionmentioning
confidence: 99%
“…Swirl systems have also been investigated for their good stability characteristics. With central fuel injection they were found to have poor combustion efficiency, high NOx and no better stability than for the jet shear layer systems (9,10). However, by injecting the fuel at the wall it was found that centrifugal forces acting on the density differences enhanced the mixing and produced improved combustion and lower NOx (11,12).…”
Section: Introductionmentioning
confidence: 99%